2022
DOI: 10.24198/pjd.vol34no2.37498
|View full text |Cite
|
Sign up to set email alerts
|

<strong>The differences of RND between males and females and the correlation between age and RND based on panoramic radiographs</strong>

Abstract: Introduction: Estimating age and sex through several radiographic methods have a significant role in the victim identification process. The mandibular ramus is thought to have a high degree of dimorphism and a close relationship with chronological age, which can be determined by ramus notch depth (RND). This study aimed to analyze the differences in RND between males and females and the correlation between age and RND based on panoramic radiographs. Methods: The type of study is an observational analytic cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Linear measurement on extraoral radiographs using the digital method was consistent with those in previous studies. 20,21 This study showed that the length of cranial base and total face height were higher in men than in women (Figure 2). This result was similar to that of a previous study, which was performed within the Indian and Colombian populations.…”
Section: Discussionmentioning
confidence: 85%
“…Linear measurement on extraoral radiographs using the digital method was consistent with those in previous studies. 20,21 This study showed that the length of cranial base and total face height were higher in men than in women (Figure 2). This result was similar to that of a previous study, which was performed within the Indian and Colombian populations.…”
Section: Discussionmentioning
confidence: 85%